Revisiting the Development of Probiotic-based Functional Chocolates - Muhammad, Dimas Rahadian Aji; Rahayu, Endang Sutriswati; Fibri, Dwi Larasatie Nur (Gifu University - United Graduate School of Agricultural Science, 2021)
The status of chocolate as functional food is still questionable for some other people as chocolate can also give some adverse effect due to its high fat and sugar content. To overcome this issue, some attempts have made by food scientist to produce chocolate with high potential health benefits and minimum adverse effects such as by fat reduction, sugar replacement and probiotic supplementation. Some of sugar replacer are providentially identified as prebiotic substances. This review, therefore, deeply discuss the potential use of probiotics and sugar replacer in chocolate. The health benefit as well as the effect on the consumer acceptance are also covered as chocolate reformulation may result in the alteration on the chocolate characteristic. Moreover, the regulation in chocolate manufacturing and functional food from different regulatory boards are covered in this review as the guidelines to answer challenges and opportunities in developing functional chocolate. This review also clearly shows a possible direction of designing probiotic chocolate in the future that has not been fully explored until to date.